Dual peptide-dendrimer conjugate inhibits acetylation of transforming growth factor β-induced protein and improves survival in sepsis. (July 2020) - Lee, Wonhwa; Park, Eun Ji; Kwon, Oh Kwang; Kim, Hyelim; Yoo, Youngbum; Kim, Shin-Woo; Seo, Young-Kyo; Kim, In-San; Na, Dong Hee; Bae, Jong-Sup
Abstract: Sepsis is a potentially fatal complication of infections and there are currently no effective therapeutic options for severe sepsis. In this study, we revealed the secretion mechanism of transforming growth factor β-induced protein (TGFBIp) that was recently identified as a therapeutic target for sepsis, and designed TGFBIp acetylation inhibitory peptide (TAIP) that suppresses acetylation of lysine 676 in TGFBIp. To improve bioavailability and biodegradation of the peptide, TAIP was conjugated to polyamidoamine (PAMAM) dendrimers. Additionally, the cell-penetrating peptide (CPP) was conjugated to the TAIP-modified PAMAM dendrimers for the intracellular delivery of TGFBIp. The resulting nanostructures, decorated with TAIP and CPP via poly(ethylene glycol) linkage, improved the mortality and organ damage in the septic mouse model and suppressed lipopolysaccharide-activated severe vascular inflammatory responses in endothelial cells. Thus, the dendrimer-based nanostructures for delivery of TAIP using CPP show great promise in practical applications in sepsis therapy.